Pelatihan dan Pendampingan Penyusunan Cost Of Goods Sold untuk Menentukan Harga Jual Produk pada Usaha Tenun di Kecamatan Sidemen Kabupaten Karangasem - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi; Diatmika, I Putu Gede (International Journal of Community Service Learning, 2018)
In general, community service program aims to provide training and assistance for the preparation of Cost Of Goods Sold (Cost of Production) to Determine the Price of Selling Products on Traditional Weavers Business in Sidemen District, Karangasem Regency. The method used in this activity is the direct practice method. The material provided during the training and assistance includes: (1) the importance of bookkeeping and the benefits of its use in running the business; (2) how to calculate the cost of production for the product; (3) cost information required in controlling production costs. The result of the activity shows that: after the training activity is done, the craftsman community's skill starts to increase by 80%. Most have been able to calculate the cost of production and determine the selling price correctly.